2015
DOI: 10.1021/ja5099403
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Induced Conformational Changes with Cation Ejection upon Binding to Human Telomeric DNA G-Quadruplexes

Abstract: The rational design of ligands targeting human telomeric DNA G-quadruplexes is a complex problem due to the structural polymorphism that these sequences can adopt in physiological conditions. Moreover, the ability of ligands to switch conformational equilibria between different G-quadruplex structures is often overlooked in docking approaches. Here, we demonstrate that three of the most potent G-quadruplex ligands (360A, Phen-DC3, and pyridostatin) induce conformational changes of telomeric DNA G-quadruplexes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
135
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(153 citation statements)
references
References 59 publications
16
135
2
Order By: Relevance
“…Similar conformational changes were observed for the interaction of the telomeric quadruplex with the ligands PDS, 360A and phen-DC3 (12). Authors interpreted the observed CD spectral changes in terms of a structural rearrangement of the (3+1) form to an antiparallel G4 caused by the displacement of a K + ion from the quadruplex.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Similar conformational changes were observed for the interaction of the telomeric quadruplex with the ligands PDS, 360A and phen-DC3 (12). Authors interpreted the observed CD spectral changes in terms of a structural rearrangement of the (3+1) form to an antiparallel G4 caused by the displacement of a K + ion from the quadruplex.…”
Section: Resultssupporting
confidence: 71%
“…G4 specific ligands either stabilize the G4 structure and/or cause certain conformational rearrangements. Binding of some bisquinolinium G4 DNA ligands (360A, Phen‐DC3 and pyridostatin) can result in the restructuring of telomeric G4 into an antiparallel two-quartets fold presumably due to the displacement of metal ions (12). The destruction of all quartets in the telomeric G4 structure in sodium or a single quartet in potassium is required for anthrathiophenedione derivative binding (13).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that it is the extent of stabilization under a given set of conditions that affects the likelihood of a G4 being detected by G4-seq. The OQs detected in the presence of PDS could also reflect the binding properties and specificity of the small molecule for G4 stabilization 25 Figure 1 A schematic of the G4-seq method. In a typical G4-seq experiment, sequencing is done twice.…”
mentioning
confidence: 99%
“…In addition, several G4 gene/oncogene promoters, such as those associated with the bcl-2 gene, have been associated with cell death/apoptosis and with diseases such as neurodegeneration, autoimmune deficiencies, and cancer13. Thus, designing and developing G4 ligands or G4s-based inhibitors are a novel potential anticancer strategy1415161718.…”
mentioning
confidence: 99%
“…Some G4 ligands efficiently stabilize G-quadruplex DNA, which often leads to telomerase inhibition15161718.…”
mentioning
confidence: 99%